First report of Trypanosoma vivax outbreak in dairy cattle in São Paulo state, Brazil - Fabiano Antonio Cadioli (Revista Brasileira de Parasitologia Veterinária, 2012)
This is the first description of a Trypanosoma vivax outbreak in the state of São Paulo (municipality of Lins). Fever, jaundice, decreased milk production, weight loss, profuse diarrhea, abortion, anemia, leukocytosis and hyperfibrinogenemia were observed in the affected animals. Thirty-one cows and calves died out of a total of 1080 in the herd. Three cows showed neurological symptoms like dysmetria, ataxia, muscle weakness, ptyalism, lymph node enlargement and submandibular edema. Flagellated hemoparasites were observed in blood smears. The species was diagnosed as T. vivax by means of PCR. This T.vivax strain showed resistance to diaminazene aceturate and the infection spread quickly at the herd. From the ELISA test, 599 serum samples (98.36%) were positive for anti-T.vivax IgG antibodies. This outbreak occurred during a very dry period, which indicates that other factors were involved in the outbreak, such as absence of tabanids and large populations of Haematobia irritans and Stomoxys calcitrans. The increases in these populations may have been due to the use of biosolid waste from sugar and ethanol plants in the sugarcane plantations surrounding the dairy farm.